Minat Berwirausaha ditinjau dari Pengaruh Pendidikan Kewirausahaan dan Motivasi Berwirausaha - Ngundiati, Nuryatim; Fitrayati, Dhiah (Jurnal Pendidikan Ekonomi Undiksha, 2020)
The purpose of study was to analyze the effect of entrepreneurship education and entrepreneurial motivation on entrepreneurial interest in class XII MAN 1 Mojokerto students. This research type is a quantitative approach, total sample of 105 students. The results of study found that entrepreneurship education and entrepreneurship motivation simultaneously have a positive effect on entrepreneurial interest. Partially entrepreneurship education and entrepreneurship motivation have a positive effect with entrepreneurial interest. Entrepreneurship education and entrepreneurship motivation were able to explain the intrepreneurship interest by 63.8%, the rest is influenced by variables outside the study